EFEKTIVITAS EKSTRAK BONGGOL, BATANG, DAN KULIT BUAH TANAMAN PISANG (MUSA X PARADISIACA L.) TERHADAP PROSES PENYEMBUHAN LUKA STUDI IN VIVO: Systematic Review - Dhea Khansa N (2022)
Wound is a condition of partial or complete tissue discontinuity due to trauma or medical treatment. Poorly treated wound may cause infection and delayed wound healing so it may interfere with the appearance and function of the injured limb. Therefore effective and efficient wound management is needed, both in modern and traditional way. Indonesian people have used herbal plants for traditional medicine since ancient times. Several studies have shown the hump, stem, and peel extracts of banana (Musa X. paradisiaca L.) play a role in wound healing process. This systematic review aims to provide information on the effectiveness of extracts of hump, stem, and peel of banana in wound healing in an in vivo studies for its potential as phytomedicine in wound management. Methods: The literature search in this systematic review used online database, namely PubMed and Google Scholar, then literature was selected using PRISMA 2020 flow. The quality of the literature was assessed using JBI critical appraisal checklist. Only moderate and good category literature used in this study. Result: There are 12 literatures in moderate and good category which show the role of hump, stem, and peel extract of banana in the wound healing process through various mechanisms that are thought to be influenced by the phytochemical contained in the extract. Conclusion: the hump, stem, and peel extract of banana (Musa X. paradisiaca L.) were considered effective in wound healing in an in vivo study. This can be seen from the duration of wound healing, macroscopic and microscopic appearances.